Biologia reprodutiva de cacau-jacaré (herrania mariae - sterculiaceae) II- estudo dos insetos visitantes da flor. - Silva, Marivana Borges (Museu Paraense Emílio Goeldi, 2022)
This work aims to study the insect visitors of Herrania mariae. The data indicate which insects and their frequencies. Six collections were made during the flowering period, from September/93 to January/94. Four trees were chosen to be observed throughout the day. Collections started at 6:00 am and finished at 7:00 pm, visiting the trees at 1 hour intervals, sampling 10' per plant. Insects were collected using a vacuum cleaner and small glassware. The pollination schedule of the species, determined in previous studies, shows that the insects present during the first hours of the day are the most likely pollinators. A total of 539 insects were collected. The most abundant families were Staphylinidae, Formicidae, Chloropidae and Phoridae. The distribution of the number of individuals per family over the collection day shows Phoridae and Chloropidae as the only ones with a definite distribution pattern. In all collections, Phoridae maintained their highest frequency of visitation between 6:00 am and 8:00 am, while Chloropidae between 9:00 am and 2:00 pm. The other insects did not maintain a set frequency at specific times. From the Collections we conclude that the Phoridae are indicated as effective pollinators of Herrania mariae, assuming that pollination by other species is occasional.